Foreword - Johnson, Alexsis M. (Columbia Journal of Gender and Law, 2018)
The third annual conference of Empowering Women of Color (EWOC), Double-Consciousness: Women of Color as Advocates for Ourselves and Others, gathered law students, practitioners, and academics together to discuss and strategize around double- consciousness as a phenomenon shared among women lawyers of color yet unique to each person’s idiosyncratic and multi-faceted identities. The conference sought to address ever- present questions of balance: How do we balance our reality as private citizens who are subject to the law with our role as advocates armed with the power of the law? How do we balance our individual professional pursuits with the quest for collective advancement of our identity groups in society?